Functional specialization of UDP‐glycosyltransferase 73P12 in licorice to produce a sweet triterpenoid saponin, glycyrrhizin. (26th June 2019) - Nomura, Yuhta; Seki, Hikaru; Suzuki, Tomonori; Ohyama, Kiyoshi; Mizutani, Masaharu; Kaku, Tomomi; Tamura, Keita; Ono, Eiichiro; Horikawa, Manabu; Sudo, Hiroshi; Hayashi, Hiroaki; Saito, Kazuki; et al.
Summary: Glycyrrhizin, a sweet triterpenoid saponin found in the roots and stolons of Glycyrrhiza species (licorice), is an important active ingredient in traditional herbal medicine. We previously identified two cytochrome P450 monooxygenases, CYP88D6 and CYP72A154, that produce an aglycone of glycyrrhizin, glycyrrhetinic acid, in Glycyrrhiza uralensis . The sugar moiety of glycyrrhizin, which is composed of two glucuronic acids, makes it sweet and reduces its side‐effects. Here, we report that UDP‐glycosyltransferase (UGT) 73P12 catalyzes the second glucuronosylation as the final step of glycyrrhizin biosynthesis in G . uralensis ; the UGT73P12 produced glycyrrhizin by transferring a glucuronosyl moiety of UDP‐glucuronic acid to glycyrrhetinic acid 3‐ O ‐monoglucuronide. We also obtained a natural variant of UGT73P12 from a glycyrrhizin‐deficient (83‐555) strain of G . uralensis . The natural variant showed loss of specificity for UDP‐glucuronic acid and resulted in the production of an alternative saponin, glucoglycyrrhizin. These results are consistent with the chemical phenotype of the 83‐555 strain, and suggest the contribution of UGT73P12 to glycyrrhizin biosynthesis in planta . Furthermore, we identified Arg32 as the essential residue of UGT73P12 that provides high specificity for UDP‐glucuronic acid. These results strongly suggest the existence of an electrostatic interaction between the positively charged Arg32 and the negatively charged carboxy group of UDP‐glucuronic acid. The functional arginine residue and resultant specificity for UDP‐glucuronic acid are unique to UGT73P12 in the UGT73P subfamily. Our findings demonstrate the functional specialization of UGT73P12 for glycyrrhizin biosynthesis during divergent evolution, and provide mechanistic insights into UDP‐sugar selectivity for the rational engineering of sweet triterpenoid saponins. Significance Statement: Glycyrrhizin, a licorice‐derived sweet triterpenoid diglycoside, is one of the most important phytoconstituents in the pharmaceutical and food industries. Here, we identified UGT73P12 as the enzyme catalyzing the sugar–sugar linkage to produce glycyrrhizin from its less glycosylated precursor in the presence of UDP‐glucuronic acid, and found that Arg32 of UGT73P12 is essential for the high specificity for UDP‐glucuronic acid, which was probably acquired during evolution to enable the functional specialization of UGT73P12 for glycyrrhizin biosynthesis.